An analytical model of a double-heterostructure mid-infrared photodetector - Lal R.K.; Jain M.; Gupta S.; Chakrabarti P. (My University, 2025)
A complete analytical model of a mid-infrared (MIR) double heterostructure (DH) photodetector has been developed. The model is physics based and takes into account all the dominant mechanisms that shape the characteristics of room temperature MIR DH photodetectors. It can be used to characterize theoretically the performance of narrow bandgap III-V based semiconductor MIR photodetectors for non-telecommunication applications. The model has been applied to estimate the detectivity, photoresponse and quantum efficiency of an P+-As0.55Sb0.15P0.30/n0-I nAs0.89Sb0.11/N+-InAs0.55Sb0.15P0.30 DH MIR photodetector. The results obtained on the basis of the model are in good agreement with reported experimental findings. The simulation code developed can be used as a tool by the design engineers for useful fabrication guidelines. © 2002 Elsevier Science B.V. All rights reserved.